Traditional World-View in Dialect Semantics of Russian Word время - T. N. Bunchuk (Научный диалог)
The all-Russian lexeme время and its derivatives in the dialects of the Russian language are considered. The author believes that the semantic volume of the word, well-known to the literary language, and its dialectal counterparts may not be identical due to different discursive conditions generated by the culture. The relevance of the study is determined by the increased attention in modern linguistics to the problems of reflection of traditional culture in the language, as well as the issues of diachronic description of the vocabulary of the Russian language and the history of particular words. Based on the analysis of lexical-semantic variants of the word время and meanings of the words with - врем - root in Russian dialects the understanding of time in traditional culture is refined. It is reported that the word время in the traditional sense names not the whole period of human life from birth to death, but only the period of biological maturity associated with the ability to procreate. It is proved that the period of maturity in the people’s culture and language is assessed as a period of prosperity, which becomes the basis for the submission of the norm in human life and a landmark in the awareness of the life space of a person. It is established that the semantics of the Russian word время has accumulated the most ancient etymological meanings of the words год and пора .